ANALYSIS OF TYPES OF SUGAR AND EXPANSION OF ITS RANGE IN UKRAINE - Samilyk, Марина; Kornijenko, Дар'я (Biota. Human. Technology, 2023)
Sugar is important for human life. By consuming sugar, the human body receives a third of the energy for normal metabolism. Sugar is a strategically important product because it is a raw material for the production of many food products. However, excessive consumption of sugar is harmful. The main raw material for sugar production in Ukraine is sugar beet. Sucrose, which is the main component of beet sugar (99.6-99.9 %), does not contain biologically active components. In addition, the assortment of sugar in Ukraine is quite limited. The prospects of the sugar industry, in accordance with the agro-climatic potential, as well as under the condition of expanding the range of enriched sugar, are the basis for the gradual development of the industry and the agrarian complex as a whole. The purpose of the article is an analytical study of the assortment of sugar in the world and in Ukraine, finding ways to expand it. The methodological basis of the study is the analysis of the assortment of sugar and the systematization of information about types of sugar. The article analyzes the assortment of sugar in the world and in Ukraine, depending on the types of raw materials and methods of its enrichment. Scientific novelty lies in the fact that the world market for sugar production, both traditional and enriched, has been studied, and it has been established that the method of enriching sugar with derivatives of wild berries processing is unique and promising. Conclusions. Based on the analysis of the literature, it was established that cane sugar has the best consumer properties, among its varieties, it is recommended to use brown (unrefined) sugar as a raw material for the production of sugar-containing products. Beet sugar is widely used as a product (sweetener) and natural preservative. Depending on the size of the crystals, a wide range of sugar is produced. The current topic is the expansion of the range of sugar with regional types of raw materials. In Ukraine, only beet granulated sugar, pressed sugar and powdered sugar are produced. Currently, the range of domestically produced enriched sugar is insufficient, there are only a few producers in this area. The method of enriching sugar with derivatives of wild berries processing can significantly expand the assortment of sugar with increased biological value and solve the problem of seasonality at beet sugar factories.